Cash holdings, board governance characteristics, and Egyptian firms’ performance - Mohamed Ali Shabeeb Ali; Saleh Aly Saleh Aly; Samir Ibrahim Abdelazim; Abdelmoneim Bahyeldin Mohamed Metwally (Cogent Business & Management, 2024)
AbstractThis paper examines the impact of cash holdings and board governance characteristics on companies’ performance by Egyptian listed non-financial companies over the period 2013–2019. The researchers employed pooled ordinary least squares and two-step system GMM estimations to test their research hypotheses. Moreover, firm fixed-effects regression was conducted for robustness test. We found a significant positive impact of cash holdings, board size, board gender diversity (BGD), and board meeting frequency on companies’ performance, while board members independence is found to impact performance negatively and lead to less profits. Further, board members role duality is found to have no significant impact on Firm Performance. This paper holds potential implications for businesses based in Egypt, as well as for investors who operate within the Egyptian market, along with regulatory bodies in developing nations. The study findings contribute valuable insights to the literature on cash holdings and corporate governance. They enhance our understanding of how cash holdings and board of directors’ characteristics can influence a company’s profitability, particularly in the context of emerging markets. Additionally, the study’s focus on an emerging market provides new evidence that can be relevant to accounting researchers studying similar contextual and institutional environments in other emerging markets.